3 Clinical outcomes and myocardial recovery in energetics, perfusion and contractile function after vavle replacement surgery in severe aortic stenosis patients with diabetes comorbidity. (6th June 2022) - Jex, Nicholas; Cubbon, Richard; Chowdhary, Amrit; Thirunavukarasu, Sharmaine; Kotha, Sindhoora; Procter, Henry; Xue, Hui; Swoboda, Peter; Kellman, Peter; Greenwood, John P; Plein, Sven; Levelt, Eylem
Abstract : Background: Aortic stenosis (AS) and type 2 diabetes mellitus (DM) are increasingly frequent comorbidities in aging populations, and diabetes is associated with increased morbidity and mortality after aortic valve replacement (AVR). Although distinct pathological entities, AS and DM share common features of impaired myocardial energetics and coronary microvascular dysfunction. The mechanisms for the adverse prognostic association between AS and DM are incompletely understood but are likely to include the collective impact of DM and AS on myocardial metabolism and perfusion. Purpose: Utilizing 31phosphorus magnetic resonance spectroscopy (31P-MRS) and cardiovascular magnetic resonance (CMR), we tested the hypotheses that the collective impact of severe AS and DM on the myocardium aggravates myocardial energetic impairment, contractile dysfunction, and fibrosis, and impairs coronary microvascular function. Methods: Eighty-eight severe AS patients with (AS-DM, n=25) and without DM (Iso-AS, n=63) undergoing AVR were prospectively recruited. A further 15 healthy volunteers served as a control group. Patients with coronary artery disease or renal impairment were excluded. All participants with AS underwent 31P-MRS followed by a comprehensive CMR protocol including cine imaging, native pre- and post-contrast T1 mapping, stress and rest adenosine perfusion and late gadolinium enhancement within 1 month prior to and 6 months after AVR. Results: Demographic, biochemical and CMR/31P-MRS data are shown in Table-1. Study groups had similar age and sex distribution, and the two AS groups were matched for surgical scores and frailty scores (EURO score and Rockwood score respectively). NTproBNP levels were similarly elevated in both AS groups. Left ventricular (LV) volumes and ejection fraction (EF) were similar between the groups, with no significant difference in LV mass, wall thickness or concentricity between the two severe AS groups. The baseline differences in myocardial energetics, stress myocardial blood flow (MBF) and global longitudinal strain (GLS) are shown in Figure-1. Severe AS patients with diabetes showed greater reductions in myocardial energetics (p<0.0001), global stress MBF (p<0.0001) and more significant reductions in GLS (p=0.001) than patients with isolated severe AS. At 6 month post AVR both AS groups showed significant improvements in stress MBF (Iso-AS: p=0.002, AS-DM: p=0.002) and GLS. However, only the patients with isolated AS showed significant improvement in myocardial energetics while no significant improvements in energetics were detected in diabetes patients after AVR. Patients with severe AS were followed up for a median of 12 months. Cumulative incidence of the clinical events post AVR (a composite of cardiovascular death, stroke, heart failure admission, infective endocarditis) was significantly higher in the DM-AS group than the isolated-AS group (Hazard Ratio: 3.35; 95% confidence interval: 0.97–11.6; p=0.02). Conclusion: We compared clinical outcomes in severe AS patients with and without T2DM and investigated myocardial recovery in energetics, perfusion and contractile function after AVR. Diabetes was associated with increased morbidity and mortality after AVR. We showed here for the first time that the collective impact of T2DM and AS on the myocardium aggravates energetic impairment, coronary microvascular dysfunction and myocardial contractile dysfunction. While myocardial recovery following AVR was associated with similar improvements in perfusion and contractile function in severe AS patients with and without T2DM, post AVR improvements in energetics were only detected in isolated AS patients. However, despite the significant improvements in contractile function and perfusion after AVR in diabetes patients, these parameters remained lower in the group with diabetes comorbidity compared to isolated AS patients. Conflict of Interest: None